Screen time and myopia: A serial multiple mediator SEM analysis - Xie, Jinchen; Lu, Chuntian; Zhu, Jie (Frontiers in Public Health, 2022)
Background COVID-19 has influenced education systems worldwide, and significantly increased screen time for college students, posing a potential risk of myopia. In China, ninety percent of college students suffer from myopia. Excessive screen time changes college students' lifestyles, imposes potential health risks, and affects opportunities for employment. It is important to identify the potential correlation between screen time use and myopia among college students. Methods This paper conducted a nationwide experiment using Chinese college students and set a multiple-mediator SEM model to analyze the potential correlation between screen time and myopia. The two mediators were sedentary behavior and physical activity, respectively. Results We obtained three valuable conclusions as follows: First, there was no significant direct relationship between screen time and myopia among Chinese college students during the COVID-19 pandemic. Second, sedentary behavior and physical activity significantly predicted the increase/decrease of myopia among Chinese college students, respectively. Third, a serial multiple mediator that encompassed sedentary behavior and physical activity sequentially fully mediated the relationship between screen time and myopia. Conclusions Although there was no directly significant relationship between screen time and myopia, screen time can indirectly influence the risk of suffering myopia by influencing sedentary behavior and physical activity. Our study demonstrates the need to prevent the potential influence of overuse of electronic devices on myopia in college students, especially during the COVID-19 pandemic.